2021
DOI: 10.3390/ma14227048
|View full text |Cite
|
Sign up to set email alerts
|

Wear Behavior of a Heat-Treatable Al-3.5Cu-1.5Mg-1Si Alloy Manufactured by Selective Laser Melting

Abstract: In this study, the wear behavior of a heat-treatable Al-7Si-0.5Mg-0.5Cu alloy fabricated by selective laser melting was investigated systematically. Compared with the commercial homogenized AA2024 alloy, the fine secondary phase of the SLM Al-Cu-Mg-Si alloy leads to a low specific wear rate (1.8 ± 0.11 × 10−4 mm3(Nm)−1) and a low average coefficient of friction (0.40 ± 0.01). After the T6 heat treatment, the SLM Al-Cu-Mg-Si alloy exhibits a lower specific wear rate (1.48 ± 0.02 × 10−4 mm3(Nm)−1), but a similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…The test part (shown in Figure 2) was designed using CAD software (SolidWorks 2021, version number: 6.30.1030, Dassault Systèmes, Vélizy-Villacoublay, France) and manufactured using the SLM 125HL machine (SLM Solutions AG, Lubeck, Germany). There is also an additional factor that is very important in the case of hydraulic solutions, and at the same time, it is one of the biggest weaknesses of AM-the high surface roughness of the as-built parts [48][49][50][51][52][53][54]. In the case of H13 tool steel, Guenther et al [52] revealed that in the case of such steels, a direct correlation between surface roughness and friction coefficient, i.e., the rougher the surface was, the higher the friction force, does not take place.…”
Section: Manufacturing Process Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The test part (shown in Figure 2) was designed using CAD software (SolidWorks 2021, version number: 6.30.1030, Dassault Systèmes, Vélizy-Villacoublay, France) and manufactured using the SLM 125HL machine (SLM Solutions AG, Lubeck, Germany). There is also an additional factor that is very important in the case of hydraulic solutions, and at the same time, it is one of the biggest weaknesses of AM-the high surface roughness of the as-built parts [48][49][50][51][52][53][54]. In the case of H13 tool steel, Guenther et al [52] revealed that in the case of such steels, a direct correlation between surface roughness and friction coefficient, i.e., the rougher the surface was, the higher the friction force, does not take place.…”
Section: Manufacturing Process Descriptionmentioning
confidence: 99%
“…There is also an additional factor that is very important in the case of hydraulic solutions, and at the same time, it is one of the biggest weaknesses of AM—the high surface roughness of the as-built parts [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. In the case of H13 tool steel, Guenther et al [ 52 ] revealed that in the case of such steels, a direct correlation between surface roughness and friction coefficient, i.e., the rougher the surface was, the higher the friction force, does not take place.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that the size of the primary phase rather than hardness was a key parameter for the wear performance. Wang et al [19] also noted that the nano-sized Al 2 CuMg and Mg 2 Si phases precipitated in the matrix after the T6 heat treatment and enhanced the wear resistance of the LPBF processed Al-3.5Cu-1.5Mg-1Si alloy. However, LPBF-deposited Al-7Si-0.5Mg-0.5Cu alloy presented the best wear resistance compared to the samples subjected to solution-treated and quenched (SQ) or subsequent aging after solution-treated and quenched (SQA) heat treatment [28].…”
Section: Introductionmentioning
confidence: 97%
“…Structural materials are inevitably exposed to friction and wear conditions in the service process [19]. Therefore, the poor wear resistance of aluminum alloys is considered a severe impediment to their further application [20].…”
Section: Introductionmentioning
confidence: 99%
“…Spierings et al [ 14 ] studied the effects of different heat-treatment temperatures and holding times on the mechanical properties and microstructure of Al-Mg alloy modified with Sc and Zr, and the results showed that the static mechanical properties are exceptionally good, with Rm values exceeding 500 MPa, along with almost no build-orientation related anisotropic effects and a high ductility even in the heat-treated condition. Scudino et al [ 15 ] studied the wear behavior of Al-7Si-0.5Mg-0.5Cu alloy prepared by SLM under heat treatment. The results show that the specific wear rate of SLM Al-Cu-Mg-Si alloy after T6 heat treatment is lower, but the average friction coefficient is similar to that of Al2024 alloy after heat treatment.…”
Section: Introductionmentioning
confidence: 99%